Unlocking Success: How Work-Life Balance and Physical Environment Shape Employee Performance and Job Satisfaction at PT. Pos Indonesia (Persero) - Hemmy Fauzan; Nayla Nur Fatimah Syarif; Suhendra Suhendra; Bahrul Yaman; Supriyono Supriyono (Jurnal Al-fatih Global Mulia, 2025)
His study analyses the effect of work-life balance and physical work environment on employee performance, with job satisfaction as an intervening variable at PT POS Indonesia. This study uses primary and secondary data and is analysed by path analysis using IBM SPSS 26. The sampling technique used is non-probability sampling with the saturation method, where 42 statements were distributed via Google Forms to 148 respondents. The results showed that work-life balance has a direct effect on job satisfaction, as well as the physical work environment which also has a significant impact on job satisfaction. In addition, work-life balance and physical work environment simultaneously affect job satisfaction. Work-life balance and physical work environment each have a direct impact on employee performance. Job satisfaction also plays a role in improving employee performance. Overall, work-life balance, physical work environment, and job satisfaction simultaneously affect employee performance. Sobel test results confirm that job satisfaction can moderate the relationship between work-life balance and physical work environment on employee performance.